Marital status, cardiovascular events, and intensive blood pressure lowering among men and women in the Systolic Blood Pressure Intervention Trial. (14th October 2021) - Pareek, M; Byrne, C; Mikkelsen, A D; Dyrvig Kristensen, A M; Vaduganathan, M; Biering-Sorensen, T; Kragholm, K H; Mortensen, M B; Singh, A; Olsen, M H; Bhatt, D L
Abstract: Background: Married persons may have lower rates of mortality and cardiovascular disease (CV) than unmarried persons although data regarding potential differences between men and women are conflicting. The Systolic Blood Pressure Intervention Trial (SPRINT) found that intensive versus standard blood pressure (BP) control reduced CV morbidity and mortality in high-risk patients. We hypothesized that marital status would influence CV event risk and the impact of intensive BP control, and that these effects would vary according to sex. Purpose: To assess the risks of CV events and mortality according to marital status in a high-risk population, and to assess if marital status modified the effect of intensive versus standard BP control. Methods: SPRINT was a randomized, controlled, open-label trial of 9361 individuals at high CV risk, at least 50 years of age, without diabetes, and with a systolic BP 130–180 mmHg. Participants were randomized to either intensive or standard BP control and followed for median 3.2 years (range 0–4.8 years). The primary efficacy endpoint was the composite of acute coronary syndromes, stroke, heart failure, or CV death. Secondary efficacy endpoints included the individual components of the primary endpoint and all-cause death. Event risk according to marital status, including variation of the effects of intensive BP control, was evaluated using multivariable Cox proportional-hazards regression with interaction analyses. The group of subjects who were married or living in a marriage-like relationship served as baseline. Results: Information on marital status was available for 8762 (93.6%) individuals. A total of 4863 (55.5%) were married or in a marriage-like relationship, 3149 (35.9%) were widowed, divorced, or separated, and 750 (8.6%) were never married. Marital status did not differ between patients randomized to intensive versus standard BP control (P=0.51). The risk of the primary endpoint was not significantly affected by marital status (P>0.05), in neither men nor women (P-interaction>0.05). The same was true for its individual components except the risk of CV death which was higher among never married men (adjusted hazard ratio [aHR], 3.29, 95% confidence interval [CI]: 1.34–8.09; P=0.009; P-sex-interaction=0.99). The risk of all-cause death was higher among widowed, divorced, or separated men (aHR, 1.90, 95% CI: 1.35–2.67; P<0.001) and among never married men (aHR, 2.53, 95% CI: 1.51–4.26; P<0.001), but not women belong to these groups (P>0.05; P-sex-interaction=0.24) (Figure). Associations were not modified by age (P-interaction>0.05). Marital status did not modify the effect of intensive BP control for any of the endpoints (P-interaction>0.05). Conclusions: In SPRINT, never married men had higher risks of both CV death and all-cause death while widowed, divorced, or separated men had a higher risk of all-cause death. The risks and benefits of intensive BP control were not affected by marital status. FUNDunding Acknowledgement: Type of funding sources: None.